Multiple components of fitness improved among overweight and obese adolescents following a community-based lifestyle intervention - Howie, Erin; McVeigh, Joanne; Abbott, R.; Olds, T.; Straker, Leon (2015)
Fitness is an important component of health, and obese adolescents regularly have poor fitness. Unfortunately, few have assessed the impact of community-based lifestyle interventions on multiple components of fitness. The purpose of this study was to assess the impact of participation in a community-based intervention involving adolescents and parents on multiple components of fitness of obese adolescents. In a within-subject, waitlist controlled clinical trial with 12 months follow-up in Western Australia, participants (n = 56) completed multiple fitness measures at baseline, immediately prior to beginning an 8-week intervention and at 3, 6 and 12 months during a maintenance period. Performance on the shuttle walk was improved immediately post-intervention (increase of 42.8 m, 95% CI: 7.5, 78.2) and at 12 months post-intervention (increase of 44.6 m, 95% CI: 1.3, 87.8) compared with pre-intervention. Muscle performance of quadriceps and deltoids were improved post-intervention (increase of 1.1 (95% CI: 0.1, 2.1) kg · F and 1.0 (0.02, 2.1) kg · F, respectively) and all muscle performance measures were improved at 12 months following the intervention. There were no changes in waist circumference. A community-based lifestyle programme such as Curtin University’s Activity, Food and Attitudes Program (CAFAP) may be a viable strategy for improving fitness in overweight adolescents.